2023
DOI: 10.1111/ajae.12390
|View full text |Cite
|
Sign up to set email alerts
|

SNAP enrollment cycles: New insights from heterogeneous panel models with cross‐sectional dependence

Abstract: The Supplemental Nutrition Assistance Program (SNAP) has grown rapidly over the past 2 decades. A large literature relies on state‐level panel data on SNAP enrollment and implements traditional two‐way fixed effects estimators to identify the impact of economic conditions on SNAP enrollment. This empirical strategy implicitly assumes slope parameter homogeneity and ignores the possibility of cross‐sectional dependence in the regression error terms. The latter could feasibly arise in state‐level panel data if t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…11 Although there is some evidence that take-up rates are higher for those with lower income, there is also evidence that some of those most in need may find it difficult to comply with program requirements (Currie, 2006;Currie & Gahvari, 2008;Homonoff & Somerville, 2021) and may fall off the SNAP rolls because of administrative burden or when related programs are cut. 12 Research has shown that SNAP is countercyclical, with caseloads increasing during recessionary times and declining during economic expansions, and that participation is responsive to the policy environment (Dickert-Conlin et al, 2021;Ganong & Liebman, 2018;Hoynes & Schanzenbach, 2016;Valizadeh et al, 2024). The variation in SNAP participation and spending displayed in Figure 1 reflects both changes in economic conditions and in the policy environment over our 29-year study period.…”
Section: Goals Background and History Of Snapmentioning
confidence: 90%
See 1 more Smart Citation
“…11 Although there is some evidence that take-up rates are higher for those with lower income, there is also evidence that some of those most in need may find it difficult to comply with program requirements (Currie, 2006;Currie & Gahvari, 2008;Homonoff & Somerville, 2021) and may fall off the SNAP rolls because of administrative burden or when related programs are cut. 12 Research has shown that SNAP is countercyclical, with caseloads increasing during recessionary times and declining during economic expansions, and that participation is responsive to the policy environment (Dickert-Conlin et al, 2021;Ganong & Liebman, 2018;Hoynes & Schanzenbach, 2016;Valizadeh et al, 2024). The variation in SNAP participation and spending displayed in Figure 1 reflects both changes in economic conditions and in the policy environment over our 29-year study period.…”
Section: Goals Background and History Of Snapmentioning
confidence: 90%
“…Research has shown that SNAP is countercyclical, with caseloads increasing during recessionary times and declining during economic expansions, and that participation is responsive to the policy environment (Dickert‐Conlin et al, 2021; Ganong & Liebman, 2018; Hoynes & Schanzenbach, 2016; Valizadeh et al, 2024). The variation in SNAP participation and spending displayed in Figure 1 reflects both changes in economic conditions and in the policy environment over our 29‐year study period.…”
Section: Goals Background and History Of Snapmentioning
confidence: 99%
“…The improved model not only fully considers the impacts of various uncertain factors in the real economy and the heterogeneity of individual responses to these impacts but also expands the general form of the bidirectional fixed effects model. Based on the principles of principal component analysis and the recognition strategies provided by the existing literature [86][87][88], this study revised Equation (7) to the following form:…”
Section: Methodsmentioning
confidence: 99%